UNIFAC Model for Liquid-Liquid Phase Equilibrium of Penicillin G and 6-APA System - Lienda Aliwarga; Herri Susanto; Reynard Reynard; Agnes Veronica Victoria (Jurnal Kimia Valensi, 2019)
This study investigated the effect of pH and type of solvent on liquid-liquid phase equilibrium in the system of pure penicillin G and mixed penicillin G with 6-APA. Penicillin G extraction was carried out in a pH range of 2.0–5.0 at 4 oC using several types of solvents. The liquid-liquid phase equilibrium mathematical model is prepared assuming that a single stage of thermodynamic equilibrium occurs in a batch process of liquid-liquid extraction. The coefficient of activity was calculated by the UNIFAC method. From the experiment, it was found that the extraction process of penicillin G was strongly influenced by pH of the solution. The highest yield of extraction was achieved with different solvents in the two types of solution. For pure penicillin G system, the highest yields was obtained in n-butyl acetate solvent (95.51%) while for penicillin G mixture with 6-APA, it was obtained in methyl iso-butyl ketone solvent (92.6%). The UNIFAC model have been tested against five three-component liquid-liquid phase equilibrium systems at pH 2.0 and 2.5. It was able to estimate the concentration of penicillin G in the organic phase with a relatively average error between experiment and calculation of 8.32%